STRATEGI PENGEMBANGAN USAHA SAYUR ORGANIK PADA HIPETANIK UNGGUL SEJATI DI DESA SIDERA KECAMATAN SIGI BIROMARU KABUPATEN SIGI - Zainab Zainab; Hadayani Hadayani; Yulianti Kalaba (Universitas Tadulako, 2018)
This study aimed to analyze the strategy of developing organic vegetable industry of Organic Farmer Association UnggulSejatiwhich has been certified organic standardsat Sidera, Sigi Biromaru Sub District of Sigi Regency. Respondents were purposively selected and secondary data were collected through observation, interview, questionnaire, and Focus Group Discussion. The data then were analyzed using quantitative strategic planning matrix (QSPM). The result of the study shows that the right strategy to develop organic vegetable is on the quadrant I which support the strengths-opportunities strategy with the value of 4.46. The implemented strategy suggested is maximizing the use of facilities to increase organic vegetable products in order to support the government programs of Go Organic 2020 and 1000 Organic Villages” with the total interest of 8.853.